Modern literature epic character (typological common motive of the universal folklore) - Baltabai Abdigaziuly, Karlygash E. Abiyr,; Asem M. Elubai, Almira Kaliyeva, (Opción, 2019)
The main purpose of the article is to study the folklore motives of the historical figure. Raiymbek's typological common stories, typical of world folklore, were described based on comparative, typological analysis of the formation of heroes, heroic growth. The results of the analysis have shown that the plot structure of the novel is systematized based on similar motifs and parallels that are inherent to archaic, heroic, historical, romantic, the epic of folklore heritage, including national folklore. In conclusion, the heroic epos has a great influence on the historical genres in the compositional, plot, thematic, ideological and artistic aspects.